Therapeutic Targeting of Retinal Immune Microenvironment With CSF-1 Receptor Antibody Promotes Visual Function Recovery After Ischemic Optic Neuropathy - Tang, Yizhen; Xiao, Zebin; Pan, Li; Zhuang, Dongli; Cho, Kin-Sang; Robert, Kyle; Chen, Xiaoxiao; Shu, Lian; Tang, Guangxian; Wu, Jihong; Sun, Xinghuai; Chen, Dong F. (Frontiers in Immunology, 2020)
Retinal ischemia/reperfusion injury (RI) is a common cause of irreversible visual impairment and blindness in elderly and critical unmet medical needs. While no effective treatment is available for RI, microglial activation and local immune responses in the retina are thought to play important roles in the pathophysiology of neurodegeneration. However, it remains unclear if targeting the retinal immune microenvironments after RI is sufficient to rescue vision and present a potentially effective therapy. Here we used rodent models of RI and showed that retinal ischemia induced by acute elevation of intraocular pressure triggered an early activation of microglia and macrophages in the retina within 12 hours. This was followed by lymphocyte infiltration and increased production of pro-inflammatory cytokines. Intravitreal injection of CSF-1R neutralizing antibody (CSF-1RAb) after RI significantly blocked microglial activation and the subsequent T cell recruitment. This also led to improved retinal ganglion cell survival and function measured by cell quantification and electroretinogram positive scotopic threshold responses, as well as increased visual acuity and contrast sensitivity as assessed by optomotor reflex-based assays, when compared to the isotype-treated control group. Moreover, the administration of CSF-1RAb efficiently attenuated inflammatory responses and activation of human microglia in culture, suggesting a therapeutic target with human relevance. These results, together with the existing clinical safety profiles, support that CSF-1RAb may present a promising therapeutic avenue for RI, a currently untreatable condition, by targeting microglia and the immune microenvironment in the retina to facilitate neural survival and visual function recovery.